Nutritional and Functional Indicators and Their Association With Mortality Among Older Adults With Alzheimer's Disease - Sousa, Odete (2020)
This study investigated how different nutritional and functional status indicators are associated with mortality in patients with Alzheimer's disease (AD). A prospective cohort study was conducted among 79 community-dwelling older adults with AD. Follow-up was 60 months. Undernutrition status was evaluated by Mini Nutritional Assessment (MNA), body mass index, mid-arm muscle circumference (MAMC), calf circumference, and phase angle. Functional status was assessed by handgrip strength, and usual gait speed. Twenty-two participants died (27.8%). Results show that undernutrition (hazard ratio [HR] 5.69, 95% confidence interval [CI] 2.21-14.61), weight loss (HR 3.82, 95% CI 1.37-10.63), underweight (HR 3.24, 95% CI 1.18-8.82), low MAMC (HR 4.54, 95% CI 1.65-12.48), calf circumference 31 (HR 4.27, 95% CI 1.63-11.16), low HGS (HR 3.11, 95% CI 1.18-8.17), and low gait speed (HR 4.73, 95% CI 1.68-13.27) were all associated with mortality. In conclusion, a poor nutritional and functional status was associated with a higher risk of mortality, regardless of sex, age, marital status, education, and cognitive function.